I'm Black When I'm Singing, I'm Blue When I Ain't and Other Plays - Sanchez, Sonia, 1934- (Book collections on Project MUSE., 2010)
A collection of Sonia Sanchez's plays along with a historicizing introduction and critical essays on Sanchez's work.